2010
DOI: 10.1590/s1677-55382010000400006
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor (VEGF) and prostate pathology

Abstract: Purpose: Previous studies suggest that vascular endothelial growth factor (VEGF) circulating levels might improve identification of patients with prostate cancer but results are conflicting. Our aim was to compare serum VEGF levels across different prostate pathologies (including benign prostatic hyperplasia, prostatitis, high grade prostate intraepithelial neoplasia and prostate cancer) in patients at high risk of prostate cancer. Materials and Methods:We consecutively enrolled 186 subjects with abnormal digi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
(31 reference statements)
0
3
0
1
Order By: Relevance
“…Increased VEGF plasma levels have been shown to correlate with skeletal metastasis and poor prognosis in prostate cancer patients and VEGF expression levels in many cancer types have been shown to correlate with poorer prognosis and metastatic potential [62]. However, other studies have shown that there is no correlation between VEGF serum levels and prognosis [63, 64]. The expression of VEGF is upregulated in prostate cancer and is associated with clinical stage, Gleason score, tumour stage, progression, metastasis and survival [6567].…”
Section: Vegf and Skeletal Metastasismentioning
confidence: 99%
“…Increased VEGF plasma levels have been shown to correlate with skeletal metastasis and poor prognosis in prostate cancer patients and VEGF expression levels in many cancer types have been shown to correlate with poorer prognosis and metastatic potential [62]. However, other studies have shown that there is no correlation between VEGF serum levels and prognosis [63, 64]. The expression of VEGF is upregulated in prostate cancer and is associated with clinical stage, Gleason score, tumour stage, progression, metastasis and survival [6567].…”
Section: Vegf and Skeletal Metastasismentioning
confidence: 99%
“…Among the cell secretome proteins, vascular endothelial growth factor (VEGF) is one of the key regulators of angiogenesis and vascular permeabilization. 1,2 VEGF is often used as a biomarker to quantify clinical stages [3][4][5][6][7] and therapeutic efficacy. [8][9][10][11] In the clinic, elevated VEGF serum concentrations correlate with various cancers, [12][13][14][15][16][17] while abnormal VEGF concentrations have been found in patients with Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 99%
“…However, its low accuracy across different cut-offs depending on factors such as age or other symptoms (i.e., benign prostatic hyperplasia, prostatitis, and cystitis) has warranted identification of other biomarkers that could further contribute in deciding whether the patient should be referred to prostatic biopsy for detailed examination. Vascular endothelial growth factor (VEGF) is a growth factor that can activate endothelial cell proliferation, angiogenesis, and induce blood vessel permeabilization, which are critical stages for tumor growth and development 4 . It has been shown to be expressed in many different types of tumors, including thyroid cancer, breast carcinoma, gliomas, lung cancer, and colorectal cancer 5 - 9 .…”
Section: Introductionmentioning
confidence: 99%